THE RELATIONSHIP OF SMARTPHONE USE WITH QUALITY DISORDERS SLEEPING IN SMA NEGERI 2 PEMATANG SIANTAR - Mona Fitri Gurusinga (Jurnal Penelitian Keperawatan Medik, 2022)
Psychological problems that arise in the form of sleep disorders, anxiety, depression, and emotional stress. Sleep is one of the basic needs that everyone needs. The need for rest and sleep must be sufficient for the body to concentrate, make decisions and participate in daily activities. The type of research is descriptive analytic research using a cross sectional approach. The population in this study is all class XI IPA 1 and XI IPA 2 in SMA Negeri 2 Pematangsiantar as to function normally. Lack of sleep will have an impact on the decreased ability many as 71 people and as many as 42 people as samples with simple random sampling method. Data obtained by interview using a questionnaire and analyzed by chi square test. From the results of the chi square test (α < 0.05), it shows that there is a significant relationship between smartphone use and sleep quality disorders in adolescents (α = 0.00) and the test results show that there is a relationship between smartphone use and sleep quality disorders in adolescents ( =0.00). It is hoped that adolescents will increase their knowledge that excessive smartphone use can cause sleep quality disorders in adolescents